2010
DOI: 10.1111/j.1365-2893.2009.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Lamivudine and adefovir therapy in HBeAg-positive chronic hepatitis B patients with poor response to adefovir monotherapy

Abstract: At present, there is no consensus treatment for patients who have poor response to Adevofir dipivoxil (ADV) monotherapy and no ADV-associated mutation. The purpose of this study was to evaluate the effect of a new therapeutic strategy combining Lamivudine (LAM) and ADV in patients with HBeAg-positive chronic hepatitis B (CHB) and poor response to ADV monotherapy. Thirty-one patients with chronic hepatitis B with HBV DNA > or = 10(4) copies/mL after 48 weeks of ADV monotherapy were included and received ADV plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
(28 reference statements)
0
4
1
Order By: Relevance
“…In the present study, we provided a head-to-head comparison of LdT+ADV with 3TC+ADV in CHB patients with suboptimal response to ADV, and we found that both 3TC+ADV and LdT+ADV treatments produced greater HBV DNA suppression and higher rates of ALT normalization. As compared to our previous study on HBeAg-positive patients with suboptimal response to ADV [25], the virological response rate of patients in the present study was significantly increased, which might be correlated to the lower baseline viral load when another NA was added. Experience from the management of NA-resistance patients suggested that combination therapy could significantly delay or prevent the emergence of drug resistance [27,28].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In the present study, we provided a head-to-head comparison of LdT+ADV with 3TC+ADV in CHB patients with suboptimal response to ADV, and we found that both 3TC+ADV and LdT+ADV treatments produced greater HBV DNA suppression and higher rates of ALT normalization. As compared to our previous study on HBeAg-positive patients with suboptimal response to ADV [25], the virological response rate of patients in the present study was significantly increased, which might be correlated to the lower baseline viral load when another NA was added. Experience from the management of NA-resistance patients suggested that combination therapy could significantly delay or prevent the emergence of drug resistance [27,28].…”
Section: Discussioncontrasting
confidence: 71%
“…However, data on the comparison of different combination strategies is rare. Previously, our two independent short-term studies on patients with poor response to ADV demonstrated that higher proportions of patients in the LdT+ADV group achieved a virological response at week 24 than did patients in the 3TC+ADV group (66.7% [16/24] versus 35.5% [11/31]) [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing that despite dose reduction, our patients with renal dysfunction had no significant increase in HBV DNA, suggesting that the efficacy of adefovir in such patients may have been more profound, some 90% of these patients were HBV DNA‐negative compared to only 66% who did not have adefovir‐related abnormal serum creatinine. This observation could be important as adefovir is considered a relatively weak antiviral agent against hepatitis B virus, and poor responders have been documented …”
Section: Discussionmentioning
confidence: 99%
“…Combination therapies are suggested to delay or prevent drug resistance and may offer a potential action for the management of suboptimal response to monotherapy [28][29][30]. Adding on LAM in patients with poor response to ADV could markedly decrease the level of HBV DNA with 2.03 log 10 copies/mL, as well as improve the response rates with 35.5% in VR and 100% in BR at 24 weeks [21]. Chen et al [31] also evaluated two different combination therapies in patients with suboptimal response to ADV.…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients revealed insufficient or poor response for initial ADV therapy after 24–48 weeks. This is partly because of the suboptimal doses, high pretreatment HBV DNA levels and ADV‐resistant variants . Thus, it is strongly recommended that therapies should be optimized by detection of serum HBV DNA during NAs treatment and 48 weeks after initial treatment is the most important time point to assess effect in ADV therapy .…”
Section: Discussionmentioning
confidence: 99%